2016
DOI: 10.1016/j.amjmed.2016.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Sexual Function in Postmenopausal Women

Abstract: BACKGROUND Limited literature suggests sexual dysfunction in women covaries with the metabolic syndrome. This study examined the association of sexual function with metabolic syndrome and cardiovascular disease in healthy older women. METHODS 376 postmenopausal, community-dwelling women from the Rancho Bernardo Study (mean baseline age = 73) completed a clinic visit during 1999 – 2002 and returned the Female Sexual Function Index (FSFI) questionnaire mailed in 2002. RESULTS 39% reported being sexually acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 35 publications
0
15
0
4
Order By: Relevance
“…Principally women with systemic arterial hypertension presented a greater rate of FSD, evaluated by the Female Sexual Function Index questionnaire, versus nor-motensive women (90 and 41% respectively) and the use of antihypertensive medications was significantly related to lower prevalence of FSD [2,25,34,35,37]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Principally women with systemic arterial hypertension presented a greater rate of FSD, evaluated by the Female Sexual Function Index questionnaire, versus nor-motensive women (90 and 41% respectively) and the use of antihypertensive medications was significantly related to lower prevalence of FSD [2,25,34,35,37]. …”
Section: Resultsmentioning
confidence: 99%
“…The number of participants ranged from 88 to 2,270 women. Only 9 studies looked specifically at MS [2,25,26,27,28,29,30,31,32]. The remaining included data about components of MS [2,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, patients with sexual dysfunction had higher triglycerides values and poor glycemic control. Low sexual desire and arousal have been reported in menopausal patients with metabolic syndrome and poor lipid profile in previous studies (5,20,21). Several studies have also reported older age as a cause of sexual dysfunction in women (22,23).…”
Section: Discussionmentioning
confidence: 87%
“…El sín-drome metabólico se asocia con disminución de la actividad sexual, deseo y satisfacción. La enfermedad de la arteria coronaria parece ser más prevalente en mujeres con actividad sexual baja (32) .…”
Section: Fisiopatologíaunclassified